The factors affecting talent’s loyalty in Sales Department of companies in Viet Nam = Các nhân tố ảnh hưởng đến lòng trung thành của nhân tài trong bộ phận bán hàng của các công ty tại Việt Nam - Phạm, Thuý Hồng (2020)
Aims of research is giving the recommendations to company owners in Viet Nam to enhance talent’s loyalty, keep and retain the best employees for Sales Department. In order to suit with these aims, this thesis gives the below missions of research: Literature reviewsthe previous research on talent, talent’s loyalty, and talent’sretention. Systematize the basic theories of talent, and all the factors affecting talent’s loyalty, talent’s retention. Study the talent’s retention, employee’s retention models, thereby selecting a suitable model for measuring loyalty of talent. Survey and analyze the status oftalent’s loyalty in Sales Department of companies in Viet Namby the selected model. Limited success evaluation and cause. Give some recommendations to improve talent’s loyalty in Sales Department of companies